Brill's Companion to Hellenistic Astronomy : a The Science in Its Contexts - Bowen, Alan C.,; Rochberg, Francesca, (Brill's Companions to Classical Studies., 2019)
In Hellenistic Astronomy: The Science in Its Contexts , new essays by renowned scholars address questions about what the ancient science of the heavens was in the ancient Near East and Mediterranean worlds, and the numerous contexts in which it was pursued. Together, these essays will enable readers not only to understand the technical accomplishments of this ancient science but also to appreciate their historical significance by locating the questions, challenges, and issues inspiring them in their political, medical, philosophical, literary, and religious contexts.